The role of the Committee on the Rights of the Child in strengthening accountability for attacks on education in armed conflict - Skelton, Ann (Frontiers in Education, 2025)
Education is increasingly under attack in situations of armed conflict, with increasing incidence of schools bombed, repurposed for military use, education politicized, and children denied access to learning. This1 opinion piece examines how the UN Committee on the Rights of the Child (CRC Committee) is responding to these violations by integrating international humanitarian law (IHL), international human rights law (IHRL), international criminal law (ICL) and global accountability mechanisms into its recommendations. Drawing on recent concluding observations to the Russian Federation and Israel, the article highlights the Committee's evolving role in protecting children's right to education in conflict zones. It argues that the Committee is not only interpreting the Convention on the Rights of the Child (CRC) as a living instrument but also asserting its relevance within a broader legal and political context. The analysis concludes that the Committee remains a vital actor in the global effort to strengthen accountability in responding to attacks on education.